Gending - gending lringan Upacara Perkawinan Agung di Keraton Yogyakarta - F. Xaveria Diah K (Institut Seni Indonesia Surakarta, 2010)
Karaton Yogyakarta as a centre of javanis culture, that it stillhave many adat and tradition in a good care. Ones of them is WeddingCeremony. This ceremonial is tobe accompanied by gending gending.Every Gending-s must be played appropriate to official prosesion.The House institution use gending Karawitan, gending S mar Mantu,gending Bindri, gending Ladrang Pengantin, gending Prabu Mataramand Raja Manggala, gending Sri Kundur and gending Tedhak Saking,gending Mas Kumambang, gending Boyong, gending Kodhok Ngorek,gending Munggang, gending Sekatenan, gending Runtung, gendingKutut Manggung, gending Lambangsari, gending Bondhet and gendingSida Asih in panggih and reseption procession .All wedding ceremony in Yogyakarta House use composition ingarap saran such as gending Semar Mantu. Here is several ekslusivegending that only be played in Karaton Yogyakarta, that is Prabu Mataram,gending Raja Manggala, gending Sri Kundur. gending TedhakSaking, gending Kodhok Ngorek and gending Munggang, while othersgending that is gending Semar Mantu should be played by public peoplein reception and panggih procession. In this case, Gending-gendingwedding ceremonial accompaniment not be lost, except special Gendinggending Karaton.Keyword: Wedding, Gending acompaniment.